The Effect of the Application of the Round Table Learning Model on Short Story Writing Skills of Grade V Students of Elementary Schools in Gowa Regency - Salam, Rosdiah; Sahabuddin, Erma Suryani; Kendek, Eka Dwimerdiani (Cerdas Proklamator, 2024)
This research was conducted on the basis of a problem found at SD Inpres Pa'jokki in Gowa regency, namely the low skills of students in writing short stories. This study aims to (1) to find out the overview of the application of the round table learning model of students, (2) to find out the results of the formation of students' short story writing skills, (3) to find out the effect of the application of the round table learning model on students' short story writing skills. This study uses a quantitative approach with a quasi-experimental design. The research design used is a nonequivalent control group design. The free variability of this study is the Round Table learning model and the bound variable is the skill of writing short stories. This study uses two classes, namely the experimental class (VB) and the control class (VA), the sampling technique used in this study is purposive sampling. Data collection techniques include observation sheets and writing tests. The data collection procedures, namely pretest, treatment, and posttest, were then analyzed by descriptive statistics and inferential statistics with the help of the IMB SPSS statistics version 22 program. The results of this study show that: (1) the application of the Round Table learning model is going well. (2) students' short story writing skills in learning after being treated using the Round Table model showed that there was a difference from the category of poor to very good. This is evidenced by the results of the pretest and posttest of students' short story writing skills. (3) there is an effect of the application of the Round Table learning model on the short story writing skills of grade V students of SD Inpres Pa'jokki, Gowa regency.